2012
DOI: 10.5505/kjms.2012.03522
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low and high frequency electromagnetic fields on fracture healing

Abstract: Kırık iyileșmesiVücuttaki onarım olayları içerisinde, skar dokusu ile sonlanmadan, gerçeğe en yakın biçimde yeniden yapılanma ile karakterize olan yara iyileşmesi kırık iyileşmesidir. Kırık iyileşmesi; dayanıklılığı, oluşumu, yenilenmesi ve yapılanması çok sayıda genel ve yerel düzenleyicilere bağlı olan, hücresel yapıların karşılıklı etkileşimini içeren karmaşık bir süreçtir. Hematomenfl amasyon, yumuşak kallus, sert kallus ve yeniden şekillenme evrelerinden oluşur (Şekil-1). Bu süreç ve evreler şimdiye kadar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We encounter many studies in the literature performed using various biologic systems and addressing the effects of several energy types on bone fracture healing [ 2 , 3 ]. It has been reported that low frequency static, electric and electromagnetic fields had certain biological effects on bone cells [ 4 7 ].…”
mentioning
confidence: 99%
“…We encounter many studies in the literature performed using various biologic systems and addressing the effects of several energy types on bone fracture healing [ 2 , 3 ]. It has been reported that low frequency static, electric and electromagnetic fields had certain biological effects on bone cells [ 4 7 ].…”
mentioning
confidence: 99%